Antibiotic Resistance of Campylobacter Recovered from Faeces and Carcasses of Healthy Livestock. (18th January 2017) - Karikari, Akosua B.; Obiri-Danso, Kwasi; Frimpong, Enoch H.; Krogfelt, Karen A.
Abstract : Campylobacter is of major significance in food safety and human and veterinary medicine. This study highlighted resistance situation in the area of veterinary public health in Ghana. Using selective mCCDA agar, isolates were confirmed phenotypically on API CAMPY and genotypically by multiplex PCR of IpxA gene. The susceptibility profile of species to common and relevant antibiotics was determined by the Kirby-Bauer disk diffusion method. Cattle, sheep, goat, and pig faecal samples analysed, respectively, yielded 13.2% (16/121), 18.6% (22/102), 18.5% (25/135), and 28.7% (29/101) Campylobacter species while 34.5% (38/110), 35.9% (42/117), 23.9% (32/134), and 36.3% (37/102) were, respectively, recovered from the carcasses. Species identified in faeces were C. jejuni 35.8% (33/92), C. jejuni subsp. doylei 4.3% (4/92), C. coli 47.8% (44/92), and C. lari 12.0% (11/92). Species discovered in carcasses were C. jejuni 83.9% (125/149), C. jejuni subsp. doylei 2.0% (3/149), C. coli 6.0% (9/149), and C. lari 8.1% (12/149). Resistance ranged from 92 to 97% to the β -lactams, 7 to 69% to the quinolones, 0 to 44% to the aminoglycosides, 97 to 100% to erythromycin, 48 to 94% to tetracycline, 45 to 88% to chloramphenicol, and 42 to 86% to trimethoprim/sulfamethoxazole as 0% resistance was observed against imipenem.